Continuous wave transscleral cyclophotocoagulation versus MicroPulse (MP-TLT) in patients with blind and painful eyes with absolute glaucoma - Yang Ling; Juan Carlos Medina Perdomo; Sun Li Hua; Zhu Xin Ping; Han Chao (The Pan-American Journal of Ophthalmology)
Introduction: Diode laser cyclophotocoagulation constitutes a treatment alternative to increase the quality of life in patients with blind and painful eyes with absolute glaucoma. Materials and Methods: A retrospective comparative study was carried out in patients with absolute glaucoma of any etiology with the aim of comparing the effectiveness and safety of MicroPulse transscleral laser therapy (MP-TLT) versus continuous wave transscleral cyclophotocoagulation in eyes of patients with absolute glaucoma. A total of 104 eyes were studied and two groups were formed: 52 treated with CW and 52 eyes treated with MP. Baseline characteristics (number, proportions, mean, and standard deviation) were summarized and compared between the two groups using the Chi-square test. Results: Mean pain was 4.5 out of 10 for the group treated with CW and 5.75 for the group treated with MP. In the CW group, the success rate was 75.0% (P = 0.001); for MP, it was 70.8% (P = 0.002). A decrease in the number of topical antiglaucomatous drugs used was found for the CW group, from a mean of 2.9 eye drops ± 1 at the beginning of the study to 1.9 ± 1.2 at two years of investigation and MP from 3.1 ± 0.5 to 2.1 ± 0.5) and with acetazolamide (P = 0.001 and 0.002), respectively. Significant complications were in the CW group (hypotony in 3, 5.7% eyes, bulbar phthisis in 1, 1.9% eye, and corneal perforation 2, 3.8% eyes; P = 0.03). Conclusions: Both techniques reduced the painful component, being more stable over time with the use of continuous wave transscleral cyclophotocoagulation (CW-TSCP), which showed greater long-term intraocular pressure control, and a higher success rate, but with a significantly lower safety profile due to the number of complications presented. The number of topical antiglaucomatous drugs and acetazolamide was decreased with both procedures.